On the efficiency of bilateral interbank insurance - Castiglionesi, Fabio; Wagner, Wolf (Journal of Financial Intermediation, 2013)
This paper studies banks’ incentives to engage in liquidity cross-insurance. In contrast to previous literature we view interbank insurance as the outcome of bilateral (and non-exclusive) contracting between pairs of banks and ask whether this outcome is socially efficient. Using a simple model of interbank insurance we find that this is indeed the case when insurance takes place through pure transfers. This is even though liquidity support among banks sometimes breaks down, as observed in the crisis of 2007–2008. However, when insurance is provided against some form of repayment (such as is the case, for example, with credit lines), banks have a tendency to insure each other less than the socially efficient amount. We show that efficiency can be restored by introducing seniority clauses for interbank claims or through subsidies that resemble government interbank lending guarantees.